EFFECT OF WELDING PROCESS PARAMETERS ON TENSILE OF LOW CARBON STEEL 283 G.C - Hayyal, Hussain; M. Faleh, Nadhim (Journal of Engineering and Sustainable Development, 2022)
In this study, three welding methods are used. The purpose to investigation the effects of SMAW, SAW, and gas tungsten arc welding (GTAW) on the tensile stress of low carbon steel conforming to ASTM 283 c. 8mm thick plates are used as base material for butt welded joints. The tensile properties of the welded joints were evaluated and the results were compared by experts using the Taguchi method to design three levels of each parameter (current, voltage and displacement speed). From this research, it is found that compared to metal shielded arc welding and submerged arc welding, the pulling effect of the gas shielded welding joint of the tungsten electrode is the best. This is mainly due to the presence of The results of using analysis of variance (ANOVA) to estimate important parameters show that welding current and speed of the weld have a significant effect on tensile stress. The experimental results are in agreement with predicted results, and the maximum error is 3%.